Teacher Feedback and Self-Assessment of Students in Higher Education: Evaluative Innovation in the Initial Training of Primary Education Teachers; [Retroalimentación Docente y Autoevaluación de Los Estudiantes en Educación Superior: Innovación Evaluativa en la Formación Inicial de Profesores de Educación Primaria] - Rios-Munoz, D; Herrera-Araya, D (Revista Brasileira de Educacao, 2023)
This article analyzes the results of the teacher feedback and self-evaluation process within the framework of an innovation in evaluative practice in teacher training. The innovation was carried out in two courses of the primary education Pedagogy of a Chilean public university. With a mixed methodology, two rating scales were applied to students to assess feedback and self-assessment. In addition, individual interviews were conducted with students to deepen the contribution of innovation in their learning. Students positively value feedback and self-evaluation since they allow the development of a reflective, critical, and self-critical pedagogical training. However, there are problems regarding the ability of feedback to strengthen its performance and its integration into the meta-evaluation process. It is concluded that the development of evaluative innovations is important to improve the initial training of teachers. © (2023) Associação Nacional de Pós-Graduação e Pesquisa em Educação – ANPEd Este es un artículo de acceso abierto distribuido en términos de licencia Creative Commons.